[Conférence internationale du chômage - Paris, 18-21 Septembre 1910] (1910)
Kongressprogramme sowie Resolutionen (1910-1911) [Konferenz/Konferenzen/Fachkonferenz/Fachkonferenzen/Arbeitsbeschaffung/Arbeitslosigkeit/Arbeitsloser/Arbeitsloser/Arbeitslose/Massnahmen gegen die Arbeitslosigkeit]